Frasa Bahasa Wate: Phrase of Wate Language - Maturbongs, Antonius (Balai Bahasa Provinsi Papua, 2023)
Various meaning and definition phrase have been made by various writer, but is not quit of congeniality phrase as a group word. In consequence, phrase basically [is] word group. If/When seen from facet forming [of] phrase, can be said that [by] phrase [is] word [relation/link] with word and word with suprasegmental elements and also situation that [do] not exceed subjek function boundary and predikat in clause. Thereby, phrase to represent word corps ( word with word, word with suprasegmental elements and situation) representing part of which not yet complete in a[n broader tuturan namely discourse and sentence (Fautngil,1997:5). Phrase only filling one function in clause. To strengthen clarification above cited one congeniality [of] phrase supporting [it] made by Elson Pickket and ( 1976: 73), namely